A violência na relação de trabalho e a proteção à personalidade do trabalhador - Alkimin, Maria Aparecida (2007)
This thesis aims to do a general approach of violence that occurs in work world, to point out its causes that vary since men s perversity, social, economic and educational factors the new model of productive and work organization introduced by globalization system as the necessity of establishing the tutelage to worker s personality, as much through juridical arrangement as through the establishment of preventive system with joint action of workers, employers and syndicates, State and others society segments. We started the work emphasizing the importance of human work to economical, social and personal development, once human work is directly linked to production and personal satisfaction. We treated Work Right evolution from the most primitive way of violence against worker person, that was slavery and whose violence, although abolished, is still practiced by many countries, including Brazil. We emphasized that ney work organization arouses the competitive spirit that could direct to a degrading work environment and inclined to violence practice; besides, many others social, cultural and educational factors and even the unemployment and sub employment social question directs to degrading ways of work, as slave or forced work, teenagers and children s work exploration, etc. We consider violence in work relationship as an attempt to human dignity and workers personality rights and in this context, we look for the due fitting in juridical, constitutional, civil and penal arrangement, concluding by the necessity of repression through law appliance and other ways of restraint, exulting violence prevention in work relationship through public and privative politics, aiming human person value